The Role of Inflammatory Biomarkers in the Assessment of Coronary Artery Disease - Napoleão, Patrícia; Selas, Mafalda; Freixo, Cláudia; Ramos, Catarina; Andreozzi, Valeska; Turkman, Antónia; Carmo, Miguel Mota; Viegas-Crespo, Ana Maria; Ferreira, Rui Cruz; Pinheiro, Teresa (IntechOpen, 2011)
None